تطور النظرية في الإدارة التربوية - الزعبي، ميسون طلاع محمود (جامعة منتوري قسنطينة, 2010)
تعرض هذه الدراسة التسلسل التاريخي لتطور النظريـة فـي الإدارة التربوية، حيث ابتدأت بالتطرق إلى الجانب النظـري لأهميـة الإدارة وأسباب ظهورها وأهم روادها.\ ثم انتقلت إلى ذكر أهم الاتجاهات والمسارات الرئيسية لتطور النظرية في الإدارة التربوية تبدأ من العصور الوسطى ثم العصور الحديثة وبما في ذلك النظرية الإسلامية للإدارة؛ وتم ذكر أهم النظريات، وخصائصها وروادها والانتقادات التي وجهت إليها، وحتى الوقت الحالي. This article presents a chronological account of the development of the educational administration theory. It starts with the study of the theoretical aspect of the importance of the administration, the causes of its most emergence and its most important pioneers. \ Then the study enumerates the most important orientations and trends of the development of the theory of educational administration starting from the Middle Ages, then the modern times, including the Islamic administration theory. Then the study presents the most important theories, their properties, their early advocates and the criticism they faced up to now.
Keywords: إدارة الجودة الشاملة -- الإدارة التعليمية -- نظرية الإدارة التربوية -- تاريخ الإدارة -- العصور الوسطى -- النظرية الإسلامية -- الفكر الإداري المقارن